Research and Applications of EUV Lithography in Silicon Photonics - Zhang, Heyi (Transactions on Computer Science and Intelligent Systems Research, 2025)
Extreme Ultraviolet (EUV) lithography is a photolithography technology used mainly in semiconductor manufacturing, especially for advanced nodes at and below 5nm. This technology holds promise for future adoption in photonic integrated circuits like silicon photonics, due to its superior resolution, overlay accuracy, and higher throughput than the current Deep ultraviolet (DUV) lithography method. While the EUV lithography system theoretically can improve the performance of silicon photonic devices such as waveguides, modulators, and photodetectors, EUV’s current use in silicon photonics is limited due to high equipment costs and several technical challenges, including material and mask compatibility, photoresist development, and patterning. This article systematically analyzes the technical principles of EUV lithography, including the principle of the light source and the steps of the photolithographic process. Meanwhile, this article looks forward to the potential of applying EUV lithography in the future of high-density silicon photonic circuits integration. It discusses the core issues of EUV-based silicon photonics fabrication. Addressing these challenges will pave the way for higher volume production, help integrate the electronic and silicon photonic ecosystem, and provide a technical reference for the development of the next generation of silicon photonics technology.